2011
DOI: 10.2190/om.63.2.c
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the Ultimate Deprivation: Narrative Themes in a Parental Bereavement Support Group

Abstract: Support groups are often used to help individuals cope with challenging and unusual life circumstances through narration. Yet, little is known about specific meta-communication within a support group setting and in what ways these interactions may benefit participants. This study uncovers narrative themes that were expressed during a series of support group meetings specific to bereaved parents. Three central narratives were revealed in the analysis including the death story narrative, coping/negotiating narra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…Many parents are, indeed, influenced to participate in ritual through social venues such as support groups and communion with other bereaved parents (Umphrey & Cacciatore, 2011). Here they are able to re-create the child's biographical sketch (Walter, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Many parents are, indeed, influenced to participate in ritual through social venues such as support groups and communion with other bereaved parents (Umphrey & Cacciatore, 2011). Here they are able to re-create the child's biographical sketch (Walter, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…As reported by others [24], some grandparents found their social networks unwilling or unable to let them talk about the loss. Like bereaved parents, they were expected to "be over" their grief in a certain amount of time [25] and perceived they should no longer be talking about their grandchild [26]. This confirmed to the grandparents the lack of recognition by society that a deceased baby in the family matters and their grief was disenfranchised [7], unrecognized as a family tragedy [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the area of groups for parents of children, the study on a social comparison in the support group for parents of children with Duchenne Muscular Dystrophy revealed a wide range of positive and negative upward and downward social comparison on illness and coping dimensions (Hodges & Dibb, 2010), while an analysis of narrative themes in a parental bereavement support group revealed that talking with members of the group about the death story, about coping/negotiating and talking in the group about experiences in communication with others outside the group enables parents' recovery after the death of the child (Umphrey & Cacciatore, 2011). …”
Section: Introductionmentioning
confidence: 99%